HTLV-1 infection and microRNAs: unraveling the complex crosstalk - Fahime Edalat; Arash Letafati; Tanin kaghazchi; Mahdieh Sadeghi; Ali Taheri; Alireza Shikki; Samira Hossein Garkani; Mehdi Afrozi; Mehdi Norouzi; Sayed-Hamidreza Mozhgani (Infectious Agents and Cancer)
Abstract Human T-cell leukemia virus type 1 (HTLV-1) retrovirus that infects millions of individuals worldwide, have caused severe diseases like adult T-cell leukemia/lymphoma (ATLL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Despite extensive research efforts, the underlying mechanisms leading to HTLV-1 pathogenesis remain incompletely understood. New research has revealed that microRNAs (miRNAs) play a crucial role in the complex interplay between HTLV-1 infection and host cellular responses. This review highlights the multifaceted interactions between HTLV-1 and miRNAs, encompassing both viral manipulation of cellular miRNA networks and host miRNA-mediated responses. Gaining a comprehensive understanding of the complex interconnection between HTLV-1 infection and miRNAs provides a significant opportunity for discovering innovative therapeutic approaches and creating advanced diagnostic tools aimed in HTLV-1 treatment.